2017
DOI: 10.1084/jem.20160462
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived miR-223 regulates intestinal inflammation via repression of the NLRP3 inflammasome

Abstract: Neudecker et al. define a role for a microRNA, miR-223, in regulating the inflammatory tone of the intestine by constraining nlrp3 inflammasome activation in CCR2+ monocytes and attenuating excessive IL-1β–driven inflammation. Therapeutic nanoparticle delivery of miR-223 mimetics limits experimental colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
282
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(294 citation statements)
references
References 50 publications
(86 reference statements)
12
282
0
Order By: Relevance
“…(18,23,42). Our data are concordant with a recent report on miR-223-mediated regulation of Nlrp3 expression and intestinal inflammation, describing Nlrp3-dependent elevation of IL-1, but not of IL-18, levels (20). The activation of both IL-1β and IL-18 requires inflammasomes and caspase-1, with NLRP3 and NLRP6 as the best-characterized representatives.…”
Section: Rag1supporting
confidence: 91%
See 2 more Smart Citations
“…(18,23,42). Our data are concordant with a recent report on miR-223-mediated regulation of Nlrp3 expression and intestinal inflammation, describing Nlrp3-dependent elevation of IL-1, but not of IL-18, levels (20). The activation of both IL-1β and IL-18 requires inflammasomes and caspase-1, with NLRP3 and NLRP6 as the best-characterized representatives.…”
Section: Rag1supporting
confidence: 91%
“…However, reduced disease severity of DSS-induced colitis was shown by other studies after treatment with anti-IL-18 antibody or IL-18-binding protein (26,27). Interestingly, the study by Neudecker et al found that IL-18 levels were unaltered by Nlrp3 expression (20). Recently, it was demonstrated that transfer of Il-18R -/-T cells did not suppress T cell transfer colitis, although IL-18R signaling was required for generation and maintenance of optimal Th1 T cell responses, indicating a possible dichotomal role of IL-18 in colitis (28).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, a very recent study reported that up-regulated expression of miR-223 in monocytes controls intestinal inflammation in inflammatory bowel disease (IBD) through repression of NLRP3 expression. 60 To confirm this finding, we used a Renilla luciferase-expressing vector with the 3' UTR sequence of human NLRP3. AGS gastric epithelial cells, which also exhibited up-regulated hsa-miR-223-3p expression in H. pylori infection, were transfected with the control and NLRP3 3' UTR vectors and luciferase activity was measured after infection.…”
Section: Discussionmentioning
confidence: 94%
“…This view is compatible with a recent study in which it was shown that a particular microRNA (miR-223) has inhibitory effects on NLRP3 function and that its absence in mice leads to increased DSS-colitis. Of interest, miR-223 levels are increased in CD patients (and in DSS-colitis), but this increase does not preclude the development of robust inflammation (25). These various studies of animal models in which decreased NLRP3 activity is shown not to lead to decreased intestinal inflammation are complemented by a study in which it was shown that increased NLRP3 activity does not lead to increased inflammation.…”
Section: Discussionmentioning
confidence: 99%